2015
DOI: 10.4269/ajtmh.14-0309
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Three Molecular Methods for the Detection and Speciation of Five Human Plasmodium Species

Abstract: Abstract. In this study, three molecular assays (real-time multiplex polymerase chain reaction [PCR], merozoite surface antigen gene [MSP]-multiplex PCR, and the PlasmoNex Multiplex PCR Kit) have been developed for diagnosis of Plasmodium species. In total, 52 microscopy-positive and 20 malaria-negative samples were used in this study. We found that real-time multiplex PCR was the most sensitive for detecting P. falciparum and P. knowlesi. The MSPmultiplex PCR assay and the PlasmoNex Multiplex PCR Kit were equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
17
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 25 publications
0
17
0
6
Order By: Relevance
“…Two subspecies of P. ovale (P. ovale curtisi and P. ovale wallikeri) are usually difficult to be distinguished by microscopy. Misidentification may also happen between different species [27]. All above may induce the unreasonable usage of antimalarial drugs and then hamper the parasite clearance and lead to the transmission of malaria, even antimalarial drug resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Two subspecies of P. ovale (P. ovale curtisi and P. ovale wallikeri) are usually difficult to be distinguished by microscopy. Misidentification may also happen between different species [27]. All above may induce the unreasonable usage of antimalarial drugs and then hamper the parasite clearance and lead to the transmission of malaria, even antimalarial drug resistance.…”
Section: Introductionmentioning
confidence: 99%
“…The two subspecies of P. ovale (P. ovale curtisi and P. ovale wallikeri) are di cult to be distinguished by microscopy. Misidenti cation may also happen between different species [30]. All of the above may induce the unreasonable usage of antimalarial drugs, hamper parasite clearance and lead to the transmission of malaria, and even antimalarial drug resistance.…”
Section: Introductionmentioning
confidence: 99%
“…By using P. knowlesi β-tubulin gene as the target gene, Iseki et al 12 managed to detect P. knowlesi down to 200 copies of DNA only. However, using 18S rRNA as the target gene, the sensitivity of LAMP was improved and managed to detect P. knowlesi DNA down to 10 copies by Lau et al 13 Real-time PCR was another approach used to detect P. knowlesi because of its low detection limit ability. Divis et al 14 reported that the analytical sensitivity for amplification of P. knowlesi-specific assay was 10 copies/μL using a TaqMan real-time PCR assay.…”
mentioning
confidence: 99%